The Role of Demographic, Economic, and Technological on Carbon Emissions in ASEAN - Alma Aurellia Amanda (Universitas Negeri Semarang, 2023)
ASEAN as a region with rapid economic growth and a large population. This study aims to analyze the factors affecting CO2 emissions in ASEAN member countries using the STIRPAT model and Panel FMOLS in the period 2014-2021. The results show that population, GDP per capita, tourism and ICT have a significant and positive influence on emissions in the long run. Meanwhile, renewables energy consumption also contributes to the reduction of CO2 emissions in the long term. However, there is a difference between CO2 emissions produced before and during the Covid-19 pandemic.